Head and neck cancer treatment in a developing country: A survey-based study in Brazil. (September 2017) - Chaves, Aline Lauda Freitas; Carvalho, Andre Lopes; Sanabria, Alvaro; Trivedi, Nirav P.; Ferrigno, Robson; Kowalski, Luiz Paulo
Highlights: Head and neck cancer is a challenging disease mainly in developing countries. There is a lack of information about this cancer treatment in these countries. A situational analysis was performed about head and neck cancer treatment in Brazil. Abstract: Background: Head and neck cancers are a heterogeneous group of diseases. There is a lack of studies providing information about the available resources to treat head and neck cancer patients in developing countries. Objective: The study aimed to describe the medical resources for treating head and neck cancer patients in Brazil. Material and methods: This is a cross-sectional study. We emailed an electronic survey to physicians with questions regarding: 1) general information about the physician and his institution; 2) treatment planning for head and neck cancers; 3) nonsurgical organ preservation strategies; and 4) treatment of head and neck squamous cell carcinoma. Results: Radiation oncologists, medical oncologists, and head and neck surgeons were equally represented; the majority of the physicians surveyed work in dedicated cancer hospitals and have a multidisciplinary cancer care team in their institution and a tumor board. Ninety-seven percent of physicians follow some guideline (mainly NCCN). The most frequently treated cancer was laryngeal cancer. Basic testing (X-ray, histopathology, CT) was available in the majority of the responders' centers, as well as health professionals (nurses, nutritionists, dentists, psychotherapists, and speech pathologists). Conclusions: The majority of the responding physicians in this survey are head and neck cancer experts and work in sites structured to treat head and neck cancer patients. However, the availability of proper treatment depends on institutional and financial issues.